Reinforced polypropylene material as well as preparation method and application thereof
By selecting a highly crystal -sized clusteryl resin in enhanced polypropylene materials, the proper margin -receiving rate of Malaysic acid anhydride closure of polypropylene and a charcoal black with suitable particle size, combined with the enhancement of glass fiber, solve the enhanced polypropylene material. The problem of stretching performance under the aging conditions of thermal oxygen is difficult to achieve, and the maintenance rate of high stretching strength and fracture erection is realized.
Patent Information
- Application Number
- CN202411528178.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-21
AI Technical Summary
The prior art is difficult to maintain the tensile properties of enhanced polypropylene materials under thermal oxygen aging conditions, especially the fluctuation of elongation at break, which makes it difficult to achieve a stable retention rate.
By selecting copolymerized polypropylene resin with higher crystallinity, maleic anhydride-grafted polypropylene with suitable grafting rate and carbon black with suitable particle size as components, combined with glass fiber reinforcement, a reinforced polypropylene material was prepared . The material is extruded and granulated through a twin-screw extruder during processing to form a material with high tensile strength and elongation at break retention.
The high -pull intensity and fracture and elongation rate of the high -pull stretching strength under thermal oxygen are realized. The stretch strength maintenance rate exceeds 96%, and the elongation rate of the breakdown is exceeded 91%, which significantly improves the stability and application range of the material and the scope of application scope. Essence
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a reinforced polypropylene material and a preparation method and application thereof. Background Art
[0002] Polypropylene has become one of the fastest growing polymers in recent years due to its simple synthesis method, abundant raw material sources, low price and good processing performance. It is widely used in automobiles, home appliances and other related industries. Reinforced polypropylene composite materials are a hot topic in the automotive industry due to their high specific strength and long fatigue resistance. They have been widely used in automotive functional parts such as sunroofs, headlights, and cooling systems.
[0003] However, during the processing, injection molding and use of polymer materials, the performance decay or appearance change caused by external environmental factors is called material aging. Research on the mechanical property retention rate of polypropylene materials under thermal oxidative aging conditions helps us improve the stability of materials and is of great significance for the development and application of materials.
[0004] There are relatively few studies on the performance retention of reinforced polypropylene materials in the prior art. In particular, the elongation at break in tensile properties is prone to large fluctuations, so a stable retention rate is the most difficult to achieve. Developing a reinforced polypropylene material with both high tensile strength retention and elongation retention is of great significance for expanding the application range of polypropylene materials. Summary of the invention
[0005] The object of the present invention is to provide a glass fiber reinforced polypropylene material having both high tensile strength retention and elongation at break retention, and a preparation method and application thereof.
[0006] The present invention is achieved through the following technical solutions: A reinforced polypropylene material, comprising the following components in parts by weight: 80 parts of copolymerized polypropylene resin; Maleic anhydride grafted polypropylene 1-5 parts; Glass fiber 5-30 parts; Carbon black 0.5-1 part; Wherein, the crystallinity of the copolymerized polypropylene resin is 36-56%; The grafting rate of maleic anhydride in maleic anhydride grafted polypropylene is 0.5-1.5wt%; The D50 particle size of carbon black is 15-70nm.
[0007] Preferably, the crystallinity of the copolymerized polypropylene resin is 42-56%.
[0008] More preferably, the crystallinity of the copolymerized polypropylene resin is 49-56%.
[0009] In the reinforced polypropylene material of the present invention, the weight percentage content of the copolymerized polypropylene resin is not less than 60wt%.
[0010] The melt index range of copolymer polypropylene resin is 25-95 g / 10min (℃, kg), the test standard is ISO1133-1:2022, temperature is 230℃, and load is 2.16kg.
[0011] The crystallinity test method of the copolymerized polypropylene resin is: testing by DSC method (differential scanning calorimetry) according to ASTM F2625-2010 standard.
[0012] Preferably, the grafting rate of maleic anhydride in the maleic anhydride grafted polypropylene is 0.8-1.2 wt %.
[0013] Maleic anhydride grafted polypropylene can be a commercial product or can be obtained by self-production. The self-production method is as follows: according to the grafting rate of maleic anhydride, add a certain amount of polypropylene, maleic anhydride, xylene, and dibenzoyl peroxide into the reactor, introduce nitrogen while stirring, and heat to 120°C for grafting reaction for 30-90 minutes to obtain a grafted product. The test method for the grafting rate of maleic anhydride is titration. The specific operation method is as follows: put the grafted material into xylene and heat it under reflux to dissolve. After cooling, add a certain amount of 0.05mol / L potassium hydroxide-ethanol solution, heat it under reflux for 8h, use 0.1% phenolphthalein solution as an indicator, and titrate to the end point with 0.05mol / L HCl-isopropanol solution while hot. The grafting rate G is calculated by the following formula: G = (N1 × Vl - N2 × V2) × M ÷ w ÷ 10 Where: N1: KOH-ethanol solution equivalent concentration, N; V1: volume of KOH-ethanol solution, ml; N2: HCl-isopropanol solution equivalent concentration, N; V2: volume of HCl-isopropanol solution, ml; M: equivalent mass of maleic anhydride, g; w: weight of the dried sample after extraction, g.
[0014] Preferably, the D50 particle size of carbon black is 20-50 nm. The test method for the D50 particle size of carbon black is: test standard GB / T19077-2016, using a laser particle size analyzer for testing.
[0015] It is possible to choose whether to add 0-1 part of processing aid according to actual conditions. The processing aid is selected from at least one of an antioxidant and a lubricant.
[0016] The antioxidant may be selected from a combination of hindered phenol antioxidants / phosphite antioxidants.
[0017] The hindered phenol antioxidant may be: antioxidant 1010, antioxidant 1076, antioxidant 1098, etc.; The phosphite antioxidant may be: antioxidant 168, antioxidant 626, antioxidant S-9228, etc.; The glass fiber can be a continuous glass fiber or a chopped glass fiber, wherein the diameter of the glass fiber can range from 8 to 18 microns, and the length of the glass fiber can range from 2 to 10 millimeters.
[0018] The preparation method of the reinforced polypropylene material comprises the following steps: according to the proportion, the components are uniformly mixed, and the reinforced polypropylene material is obtained by extruding and granulating through a twin-screw extruder. Specifically, the temperature of the screw barrel can be set to 120°C for the first zone, 190°C for the second zone, 210°C for the third zone, 210°C for the fourth zone, 210°C for the fifth zone, 230°C for the sixth zone, 230°C for the seventh zone, 230°C for the eighth zone, 220°C for the ninth zone, and the main engine speed is 300-500 rpm; the aspect ratio of the twin-screw extruder is 40:1-48:1.
[0019] The application of reinforced polypropylene materials is used to prepare parts such as kettles, headlight housings, and bumper brackets.
[0020] The present invention has the following beneficial effects: 1. The copolymer polypropylene resin with higher crystallinity is selected, which can make the material have a higher elongation at break retention rate. This is because polypropylene will undergo recrystallization at high temperature to make its crystal morphology more regular. After the crystallization is complete, the molecular chain is arranged more closely and has less room for movement, which causes the elongation to decrease. When the crystallinity of the resin is relatively high, the increase in crystallinity after hot storage is not high, and the elongation decrease is not obvious, so the elongation retention rate is higher. On the contrary, when the crystallinity of the resin is low, the increase in crystallinity of the material after hot storage is relatively higher, so the elongation decrease is more significant.
[0021] 2. Selecting a compatibilizer with an appropriate grafting rate can also enable the material to obtain a good tensile performance retention rate. When the grafting rate is too high, a tight mesh structure will be formed between the compatibilizer and the resin. This structure is not easily damaged after high-temperature heat storage, so it has a higher tensile strength retention rate. However, at the same time, the overly tight structure limits the slippage of the molecular chain, which will make its anti-deformation ability weaker and reduce the elongation at break retention rate. When the grafting rate is too low, the degree of compatibilizer coating on the resin surface is poor, the effect of glass fiber reinforcement is not ideal, resulting in poor uniformity of polypropylene molecular crystallization, and the material cannot obtain a good performance retention rate after hot storage.
[0022] 3. Selecting carbon black powder with appropriate particle size for coloring will help improve the tensile performance retention rate of the material. When the particle size of the added carbon black powder is too small, the undispersed part is easy to form agglomerates, forming crystal defects in the polypropylene resin, causing performance degradation after hot storage. When the particle size of the added carbon black powder is too large, it will also cause serious performance degradation of the material during hot storage. DETAILED DESCRIPTION
[0023] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0024] The sources of raw materials used in the present invention are as follows: Copolymer polypropylene A: K7760H produced by Yanshan Petrochemical, with a melt flow rate of 56g / 10min at 230℃ and a load of 2.16kg, and a crystallinity of 37.8%; Copolymer polypropylene B: PP EP5075X produced by China SABIC, with a melt flow rate of 60 g / 10 min at 230 °C and a load of 2.16 kg, and a crystallinity of 42.8%; Copolymer polypropylene C: PP7935E1 produced by ExxonMobil, with a melt flow rate of 60 g / 10 min at 230 ° C and a load of 2.16 kg, and a crystallinity of 48.3%; Copolymer polypropylene D: PP M60T produced by Zhenhai Refining and Chemical, with a melt flow rate of 60 g / 10 min at 230 ° C and a load of 2.16 kg, and a crystallinity of 53.5%; Copolymer polypropylene E: PP K9829H produced by Yanshan Petrochemical, with a melt mass flow rate of 28 g / 10 min at 230 ° C and a load of 2.16 kg, and a crystallinity of 33.1%; Homopolymer polypropylene: Shanghai Petrochemical HC9012, melt mass flow rate at 230℃ and 2.16kg load is 10g / 10min, crystallinity is 43.3%; Maleic anhydride grafted polypropylene A: grafting rate 0.5%, homemade; Maleic anhydride grafted polypropylene B: grafting rate 0.8%, homemade; Maleic anhydride grafted polypropylene C: grafting rate 1.2%, homemade; Maleic anhydride grafted polypropylene D: grafting rate 1.5%, homemade; Maleic anhydride grafted polypropylene E: grafting rate 0.3%, homemade; Maleic anhydride grafted polypropylene F: grafting rate 1.8%, homemade; The homemade method is: according to the grafting rate of maleic anhydride, a certain amount of polypropylene, maleic anhydride, xylene, and dibenzoyl peroxide are added to the reactor, nitrogen is introduced while stirring, the temperature is raised to 120°C for grafting reaction for 30-90 minutes to obtain maleic anhydride grafted polypropylene, and then the grafting rate of maleic anhydride is determined by titration.
[0025] Carbon black was purchased from Cabot, and raw materials with different D50 particle sizes were obtained by screening: Carbon black A: D50 particle size is 18nm; Carbon black B: D50 particle size is 25nm; Carbon black C: D50 particle size is 50nm; Carbon black D: D50 particle size is 70nm; Carbon black E: D50 particle size is 9nm; Carbon black F: D50 particle size is 102nm; Chopped glass fiber: ECS13-04-508A, Jushi Group; Antioxidant: Mass ratio of antioxidant 1010 / antioxidant 168 = 1:1.
[0026] Embodiment and comparative example The preparation method of the enhanced polypropylene material: according to the ratio, the components are mixed uniformly, and granulated by extrusion through a twin-screw extruder, the barrel temperature is set to be 120°C for zone 1, 190°C for zone 2, 210°C for zone 3, 210°C for zone 4, 210°C for zone 5, 230°C for zone 6, 230°C for zone 7, 230°C for zone 8, 220°C for zone 9, and the main engine speed is 350 rpm; the aspect ratio of the twin-screw extruder is 40:1, and the enhanced polypropylene material is obtained.
[0027] Various test methods: (1) Retention rate test method: After the reinforced polypropylene material is dried, the injection-molded tensile specimens are tested for the initial tensile strength and elongation at break. At the same time, the tensile specimens are placed in a 150°C precision aging test chamber for 400 hours, and the tensile strength and elongation at break after heat storage are tested. Based on the tensile properties before and after heat storage, the performance retention rate is calculated by the following formula. Performance retention rate = test data after heat storage / test data before heat storage × 100%.
[0028] Table 1: Components (parts by weight) and test results of reinforced polypropylene materials of Examples 1-6 Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Copolymer Polypropylene A 80 80 80 Copolymer polypropylene B 80 Copolymer polypropylene C 80 Copolymer polypropylene D 80 Maleic Anhydride Grafted Polypropylene A 3 1 5 3 3 3 Fiberglass 20 5 30 20 20 20 Carbon Black A 0.8 0.5 1 0.8 0.8 0.8 Antioxidants 0.2 0.2 0.2 0.2 0.2 Tensile strength retention, % 97.3 96.5 98.3 98.2 98.5 98.6 Elongation at break, % 91.9 92.5 91.2 95.8 96.2 96.5 It can be seen from Examples 1 / 4 / 5 / 6 that the crystallinity of the copolymerized polypropylene resin is preferably 42-56%, more preferably 49-56%.
[0029] Table 2: Components (parts by weight) and test results of reinforced polypropylene materials of Examples 7-12 Example 7 Example 8 Example 9 Example 10 Embodiment 11 Example 12 Copolymer Polypropylene A 80 80 80 80 80 80 Maleic Anhydride Grafted Polypropylene A 3 3 3 Maleic Anhydride Grafted Polypropylene B 3 Maleic Anhydride Grafted Polypropylene C 3 Maleic Anhydride Grafted Polypropylene D 3 Fiberglass 20 20 20 20 20 20 Carbon Black A 0.8 0.8 0.8 Carbon Black B 0.8 Carbon Black C 0.8 Carbon Black D 0.8 Antioxidants 0.2 0.2 0.2 0.2 0.2 0.2 Tensile strength retention, % 97.8 97.9 98.1 97.5 97.9 97.6 Elongation at break, % 93.4 93.6 91.7 92.6 92.9 92.0 It can be seen from Examples 1 / 7 / 8 / 9 that as the grafting rate of maleic anhydride in maleic anhydride grafted polypropylene increases, the tensile strength increases, but the elongation at break first increases and then decreases. The optimal grafting rate is 0.8-1.2 wt %.
[0030] It can be seen from Examples 1 / 10 / 11 / 12 that the preferred carbon black particle size D50 is 20-50 nm.
[0031] It can be seen from the above examples that the tensile strength retention rate of the reinforced polypropylene material of the present invention is greater than 96%, and the elongation at break retention rate is greater than 91%.
[0032] Table 3: Components (parts by weight) and test results of reinforced polypropylene materials of comparative examples 1-6 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Copolymer Polypropylene A 80 80 80 80 Copolymer polypropylene E 80 Homopolymer Polypropylene 80 Maleic Anhydride Grafted Polypropylene A 3 3 3 3 Maleic Anhydride Grafted Polypropylene E 3 Maleic Anhydride Grafted Polypropylene F 3 Fiberglass 20 20 20 20 20 20 Carbon Black A 0.8 0.8 0.8 0.8 Carbon Black E 0.8 Carbon Black F 0.8 Antioxidants 0.2 0.2 0.2 0.2 0.2 0.2 Tensile strength retention, % 95.5 100.5 92.8 97.4 94.1 89.8 Elongation at break, % 83.8 80.7 91.5 86.3 90.8 90.5 It can be seen from Comparative Example 1 that if the crystallinity of the copolymerized polypropylene is too low, the tensile strength retention rate and the elongation at break retention rate are both very low.
[0033] It can be seen from Comparative Example 2 that even if the crystallinity of homopolypropylene is within the scope of the present invention, the elongation at break retention is very poor because homopolypropylene itself has the characteristic of being easily brittle, resulting in poor ability to maintain its deformation rate.
[0034] It can be seen from Comparative Examples 3 / 4 that if the grafting rate of maleic anhydride grafted polypropylene is not within the scope of the present invention, the technical effect of the present invention cannot be achieved.
[0035] It can be seen from Comparative Examples 5 / 6 that if the D50 particle size of carbon black is not within the scope of the present invention, the technical effect of the present invention cannot be achieved.
[0036] Table 4: Components (parts by weight) and test results of reinforced polypropylene materials in comparative examples 7-8 Comparative Example 7 Comparative Example 8 Copolymer Polypropylene A 80 80 Maleic Anhydride Grafted Polypropylene A 0 7 Fiberglass 20 20 Carbon Black A 0.8 0.8 Antioxidants 0.2 0.2 Tensile strength retention, % 78.2 98.4 Elongation at break, % 90.1 89.3 It can be seen from Comparative Example 7 that the tensile strength retention rate is too low when no maleic anhydride grafted polypropylene is contained.
[0037] It can be seen from Comparative Example 8 that if the content of maleic anhydride grafted polypropylene is too high, the elongation at break will be too low.
Claims
1. A reinforced polypropylene material, characterized in that: By weight, it includes the following components: 80 parts of copolymerized polypropylene resin; Maleic anhydride grafted polypropylene 1-5 parts; Glass fiber 5-30 parts; Carbon black 0.5-1 part; Wherein, the crystallinity of the copolymerized polypropylene resin is 36-56%; The grafting rate of maleic anhydride in maleic anhydride grafted polypropylene is 0.5-1.5wt%; The D50 particle size of carbon black is 15-70nm.
2. The reinforced polypropylene material according to claim 1, characterized in that: The crystallinity of the copolymerized polypropylene resin is 42-56%.
3. The reinforced polypropylene material according to claim 1, characterized in that: The crystallinity of the copolymerized polypropylene resin is 49-56%.
4. The reinforced polypropylene material according to claim 1, characterized in that: The grafting rate of maleic anhydride in the maleic anhydride grafted polypropylene is 0.8-1.2wt%.
5. The reinforced polypropylene material according to claim 1, characterized in that: The D50 particle size of carbon black is 20-50nm.
6. The reinforced polypropylene material according to claim 1, characterized in that: By weight, it includes 0-1 part of processing aids.
7. The method for preparing the reinforced polypropylene material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: mixing the components uniformly according to the proportion, extruding and granulating through a twin-screw extruder to obtain a reinforced polypropylene material.
8. Use of the reinforced polypropylene material according to any one of claims 1 to 6, characterized in that: Used to prepare kettles, headlight housings, and bumper brackets.
Citation Information
Patent Citations
Glass fiber reinforced co-polypropylene composite material and preparation method of the Glass fiber reinforced co-polypropylene composite material
CN102181100A
Glass fiber reinforced low-temperature-resistant polypropylene material, preparation method of glass fiber reinforced low-temperature-resistant polypropylene material and application of glass fiber reinforced low-temperature-resistant polypropylene material in preparation of automobile pedals
CN105153549A
Reinforced polypropylene material and preparation method thereof
CN111534037A
Energy-saving regenerated polypropylene composite material and preparation method thereof
CN114539678A
Fiber composite material
CN117777592A